Rolling-out PDPA compliance programme: business issues and practical challenges to manage - between failed, half-baked & sustainable PDPA roll-out - Zulhuda, Sonny (2015)
The Personal Data Protection Act (PDPA) 2010 has been in force since November 2013. Now is the time to talk about compliance. This talk discusses the key issues and challenges for business entities and commercial players in preparing themselves to comply with the requirements of data processing brought about by the PDPA 2010.